2014
DOI: 10.1152/ajpheart.00987.2013
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of central blood volume and implications for respiratory control function

Abstract: The respiratory operating point (ventilatory or arterial PCO 2 response) is determined by the intersection point between the controller and plant subsystem elements within the respiratory control system. However, to what extent changes in central blood volume (CBV) influence these two elements and the corresponding implications for the respiratory operating point remain unclear. To examine this, 17 apparently healthy male participants were exposed to water immersion (WI) or lower body negative pressure (LBNP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
6
28
0
Order By: Relevance
“…Therefore, it seems that the change in P ET ,CO2 observed during these experimental conditions is likely to reflect changes in P aC O2. Robbins, Conway, Cunningham, Khamnei, & Paterson () reported that P ET ,CO2 consistently underestimated P aC O2, a finding that is consistent with our studies (Miyamoto et al., , ). Jones, Robertson, & Kane () reported that P ET ,CO2 is higher than P aC O2 when FI,CO2 is increased, whereas it is lower in normal conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it seems that the change in P ET ,CO2 observed during these experimental conditions is likely to reflect changes in P aC O2. Robbins, Conway, Cunningham, Khamnei, & Paterson () reported that P ET ,CO2 consistently underestimated P aC O2, a finding that is consistent with our studies (Miyamoto et al., , ). Jones, Robertson, & Kane () reported that P ET ,CO2 is higher than P aC O2 when FI,CO2 is increased, whereas it is lower in normal conditions.…”
Section: Discussionsupporting
confidence: 91%
“…First, in the methods determining CVR that use P ET ,CO2, this is based on the notion that P ET ,CO2 is closely related to P aC O2. Although the P ET ,CO2 estimate of P aC O2 might have limitations in the present study, our previous studies revealed that P ET ,CO2 was tightly correlated with P aC O2 throughout the hypercapnic and hypocapnic range during hypercapnia and hyper‐ and hypoventilation across various experimental conditions (Miyamoto et al., ). Therefore, it seems that the change in P ET ,CO2 observed during these experimental conditions is likely to reflect changes in P aC O2.…”
Section: Discussionmentioning
confidence: 90%
“…One possible explanation is lower CO 2 reactivity in VA compared with that of ICA (Sato et al 2012b). It is well established that orthostatic stress causes hypocapnia with hyperventilation (Ogoh et al 2013a;Miyamoto et al 2014), and both arteries should vasoconstrict during orthostatic stress, although hypoperfusion is not caused solely by a lower arterial partial pressure of CO 2 (Immink et al 2006). In the present study, however, VA blood flow may react only to the lower arterial partial pressure of CO 2 caused by high hyperventilation during high orthostatic stress (−50 mmHg LBNP).…”
Section: Discussionmentioning
confidence: 99%
“…The intersection point between the controller and plant curves predicts the closed-loop operating point of respiration (G and H). LBNP moved the operating point of the respiratory equilibrium diagram leftwards, indicating that a decrease in central blood volume (CBV) reduced PETCO2 without changing V ・ E. This finding provides the evidence that these respiratory and cardiovascular responses to CBV shifts are related to alterations in the elements of both controller and plant subsystems in the respiratory chemoreflex system 15) . Importantly, the plant curve was unchanged around the operating point during LBNP despite the downward shift in the modified metabolic hyperbola.…”
Section: Functional Evaluation Of the Respiratory Chemoreflex Feedbacmentioning
confidence: 64%
“…(Reprinted from Ref. [15]) Fig. 9 Determination of equilibrium (steady-state) values of V ・ E and PaCO2 during light-and heavy-intensity exercise.…”
Section: Systems Approach To Analysis Of Respiratory Control During Ementioning
confidence: 99%